Pengaruh Pelapisan Nano-Emulsi Minyak Wijen dan Sereh Terhadap Karakteristik Fisiko-Kimia dan Sensoris Pascapanen Pisang Cavendish (Musa Acuminata, L.) - I Kadek Krisna Rupawan; I Made Supartha Utama; I Wayan Widia; Ni Made Defy Janurianti (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2024)
Cavendish banana fruit is a climatic fruit characterised by high ethylene production. The high respiration rate triggers the postharvest ripening process which results in the rapid physiological deterioration of the fruit. The objectiv e of this study was to determine the effect of sesame oil and lemongrass oil nano - emulsions on the postharvest physico - chemical and sensory characteristics of Cavendish banana fruit. The research design used was a completely randomised design (CRD) with tw o treatment factors. First, sesame oil concentration factor (W) consisting of 0%, 0.5%, and 1% concentrations, second, lemongrass oil treatment factor (S) consisting of 0%, 0.5%, 1%, and 1.5% concentrations with three replications of the treatment so that there were 36 samples. Physico - chemical parameters observed included weight loss, fruit hardness, colour difference, total soluble solids (TPT), and total acid, and sensory parameters included sweetness and aroma of the fruit. The results showed that sesam e oil and lemongrass oil nano - emulsion coating significantly affected the weight loss, fruit hardness, colour difference, TPT, total acid, and sensory values of Cavendish banana fruit. Fruit coating with 1% sesame oil and 1% lemongrass oil concentration (W 2S2) was the best concentration in maintaining weight loss, fruit hardness, colour difference, and total acid with average values of weight loss (25.04%), fruit hardness (10.47 kg/cm2), colour difference (58.8%), total acid (4.67%). The treatment with a mi xture of 0.5% sesame oil and 1% lemongrass oil (W1S2) was the best combination in maintaining the TPT value with an average value of 23.50% during 12 days storage and the control received the highest score in the sensory test on day 9 with an average value of 5.